Optimized Design of the Reliability of Axle Gearbox in JMY175 Industrial Diesel Locomotive - Guo Hongxian; Cun Ligang; Liu Yanhu; Chen Shuaiyu (Jixie chuandong)
Taking JMY175 industrial diesel locomotive for example,the structure composition of the axle gearbox is introduced. According to the reliability theory and the modern mechanical design optimization method,taking the volume,reliability,coincidence degree of the gear transmission as the target function,taking the gear parameter as design variables,reliability optimization design of the axle gearbox is carried out. The reliability of gear fatigue strength is combined within the constraint conditions,the optimal solution of the parameters is obtained,the results show that the volume is reduced by 35. 71%,and the reliability is improved by 2. 7074%,and the coincidence degree is increased by 12. 68%. The goals of reducing production cost,improving the stability of gear transmission and prolonging the service life of the gearbox are realized.